Screening for native Trichoderma strains as potential biocontrollers of the olive pathogen Verticillium dahliae - Carrasco, Franca Denise; Miranda, Victoria; Sede, Silvana M.; Bustos, Sebastian; González, Valeria; Otero, Maria Laura; Fracchia, Sebastián (Taylor and Francis, 2024)
Verticillium dahliae is a soilborne pathogen that causes significant losses in olive crops in northwestern Argentina. Biological control through antagonistic microorganisms such as Trichoderma has great potential in the management of Verticillium wilt of olive. This investigation aims to isolate, identify and characterize native Trichoderma strains for biocontrol of V. dahliae. Thirty-nine Trichoderma strains were isolated from soils of olive orchards and natural areas and they were morphologically and molecularly characterized. Desired attributes for plant growth and bioprotection, such as indole acetic acid (IAA) production, endophytism and antagonistic potential against the pathogen were evaluated. Thirteen Trichoderma species were identified, belonging to the Trichoderma, Longibrachiatum, Virens, and Harzianum clades. Physiological characterization revealed that fourteen strains produced IAA while ten showed endophytic capacity. The antagonistic parameters quantified were very variable: eight strains showed high growth inhibition values (PI > 65%), while six strains reached mycoparasitism (PM) values higher than 90% for both pathogens. Three endophytic strains exhibited IAA production and antagonistic activity against V. dahliae, becoming potential candidates for bioprotection of olive orchards. Olive cultivation in the arid regions of northwestern Argentina is subjected to strong stress conditions mainly due to the type of soils with low organic matter content and water retention. Thus, selected Trichoderma strains with more than one beneficial attribute are a fundamental tool for sustainable olive cultivation, not only as antagonists of emerging pathogens but also as mitigators of abiotic stress conditions that prevail in these environments.